Performance of Shusama Organic Fertilizer on the Growth and Yield of Wetland Rice (Dhaka University Journal of Biological Sciences, 2011)
Studies on the performance of Shusama organic fertilizer on the growth and yield of wetland rice was carried out during the T. aman season. The modern rice variety BRRIdhan 31 was used as test crop. The following eight treatment combinations were tested: T1 = Native nutrient; T2 = Soil Test Base (STB); T3 = 1/3rd of STB + Shusama @ 124Kg/ha; T4 = 1/3rd of STB + Shusama @ 124 Kg/ha as basal and 250 g/decimal at 40 ? 45 DAT; T5 = 25% STB + Shusama @ 124 Kg/ha; T6 = 50% STB + Shusama @ 124 Kg/ha; T7 = 75% STB + Shusama @ 124 Kg/ha; T8 = 100% STB + Shusama @ 124 Kg/ha. The experiment was laid out in Randomized Complete Block Design with 3 replications of each treatment. It appeared from the results that 50% reduction of chemical fertilizer on STB along with Shusama @ 124 Kg/ha may be a good combination of organic and inorganic fertilizer for sustaining soil fertility and increasing T. aman rice.Key words: Organic fertilizer; Growth; Yield; Wetland riceDOI: http://dx.doi.org/10.3329/dujbs.v20i1.8833Dhaka Univ. J. Biol. Sci. 20(1): 15-21, 2011 (January)